2016
DOI: 10.1055/s-0042-114221
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Polypharmacy in Female Patients with Overactive Bladders – Cross-Sectional Study in a Specialist Outpatient Department

Abstract: Background: The consumption of certain drugs can cause urinary incontinence. The aim of this study is to determine the frequency of consumption of drugs that can favour incontinence, the incidence of polypharmacy and the incidence of potentially dangerous drug-drug interactions in female patients suffering from overactive bladder (OAB) who presented to a urogynaecological outpatient department. Methods: We undertook a retrospective case series study. The data from 100 female patients who attended the urogyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…In a study evaluating the frequency of drugs that can exacerbate incontinence, prevalence of polypharmacy and adverse drug events in female patients with overactive bladder; researchers showed that 57 % of the patients were using at least one drug that could exacerbate urinary incontinence. The prevalence of polypharmacy was 38 %, while 45 % of the patients had drug-drug interactions that can disrupt the quality of life (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the frequency of drugs that can exacerbate incontinence, prevalence of polypharmacy and adverse drug events in female patients with overactive bladder; researchers showed that 57 % of the patients were using at least one drug that could exacerbate urinary incontinence. The prevalence of polypharmacy was 38 %, while 45 % of the patients had drug-drug interactions that can disrupt the quality of life (27).…”
Section: Discussionmentioning
confidence: 99%
“… 38 Fourth, another possible mechanism is polypharmacy (often defined as the prescription of ≥5 different drugs), as polypharmacy is strongly associated with multimorbidity, 39 while the frequency of polypharmacy is high among patients attending a specialist outpatient department for UI. 40 Fifth, sarcopenia could also have a mediating role in the association between multimorbidity and UI, as previous studies have found associations of sarcopenia with both multimorbidity 41 and UI. 42 Sixth, another important factor is physical activity, as less physical activity is associated with a higher prevalence of multimorbidity 43 and UI.…”
Section: Discussionmentioning
confidence: 92%
“…Polypharmacy affects approximately 40% of older women and is a significant health concern given the risk of severe adverse events [27, 28]. Drugs commonly prescribed to older women can alter normal bladder function, worsen OAB symptoms, or adversely interact with standard OAB pharmacotherapy.…”
Section: Clinical Considerations For Older Women With Oabmentioning
confidence: 99%